Effect of halides on nanoporous Zn-based catalysts for highly efficient electroreduction of CO2 to CO - Dang Le Tri Nguyen; Jee, Michael Shincheon; Won, Da Hye; Oh, Hyung-Suk; Min, Byoung Koun; Hwang, Yun Jeong (ELSEVIER SCIENCE BV, 2018)
The effects of halide ions (F-, Br-, or I-) on nanoporous Zn-based electrocatalysts were assessed. All catalysts in the presence of halides exhibited high electrocatalytic performances of CO2 reduction reaction (CO2RR) and efficient suppression of hydrogen evolution reaction (HER) with a maximum Faradaic efficiency of up to 97%. The increasing adsorption strength from F- to I- is proposed to form more porous structures and higher oxidized Zn species, thus facilitating the protonation of CO2 and stabilizing the adsorbed intermediates induced by charge donation from the adsorbed halides on Zn surface to CO2, enhance CO2RR and simultaneously suppress HER.
Keywords: CARBON-DIOXIDE; ELECTROCHEMICAL REDUCTION; OXIDE; SELECTIVITY; OXYGEN; ELECTROCATALYST; ENVIRONMENT; TRANSPORT; FILMS; CU